Keterkaitan Identitas Sosial dan Resiliensi pada Individu Dewasa Awal Generasi Z - Syarifah Najmah Khairiyyah; Agoes Dariyo (Lembaga Yasin AlSys, 2026)
Generation Z is entering early adulthood amid complex and dynamic psychological challenges in the digital era, yet is often stigmatized as a “strawberry generation” perceived as fragile, sensitive, and unable to withstand life’s pressures. Social identity as part of a social group has the potential to serve as a source of strength and psychological support, but its association with psychological resilience among Generation Z in Indonesia has not been extensively examined. This study aimed to determine the significant relationship between social identity and psychological resilience among early adult members of Generation Z. A quantitative approach with a correlational design was employed, involving 535 Generation Z individuals aged 18–25 years residing in the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang, and Bekasi). Data were collected online using the 11-item Social Identity Scale to measure social identity and the 25-item Connor–Davidson Resilience Scale to measure psychological resilience. The main data analysis was conducted using Spearman’s rank correlation, while additional analysis employed Pearson’s correlation after classical assumption testing (validity, reliability, normality, and linearity). The results showed that respondents had moderate to high levels of social identity (M = 53.90; SD = 8.64) and high levels of psychological resilience (M = 100.07; SD = 12.21). Furthermore, a significant positive relationship was found between social identity and psychological resilience among early adult members of Generation Z, indicating that a strong and positive social identity can enhance individuals’ resilience in facing pressure, stress, and various life challenges.